Processing of Corn Cobs Waste into Briquettes Using Cob Press Machine Capacity 40 kg / hour - Yasinta Sindy Pramesti; Bambang kristanto; Heru Pratama (Procedia of Engineering and Life Science, 2021)
Along with economic growth and population growth, it will continue to increase, it will lead to an increase in energy consumption in all sectors of life. Indonesia is known as an agricultural country, where most of its territory is in the form of wide and fertile agricultural lands with the majority of the population as farmers. One of the wastes generated from the agricultural sector is corn cobs. The large amount of corn cobs waste produced by farmers in the Ngunut District of Tulungagung Regency is a loss if it is not converted to something more efficient and useful. This study aims to design a tool that can convert corn cobs waste into briquettes. Based on the results of research that has been done, the corncob charcoal press machine that is made has a capacity of 40 kg / hour. This machine has a bore diameter of 35 mm and a bore depth of 17 mm. The resulting roll rotation speed reaches 4.15 rpm.